The Antecedents of Purchase Intention on Small and Medium Enterprises Product During Pandemic Covid-19 in Denpasar City - Wayan Ardani (PINISI Discretion Review, 2022)
The Covid-19 pandemic has plunged the world into a global economic crisis. The recession has hit businesses, including small and medium enterprises (SMEs). Some SMEs are successfully capitalizing on economic crises by turning crises into opportunities.. This study aims to determine the role of eWOM in mediating the influence of social media and brand image on purchase intention of SMEs products. A survey was conducted from customers who experienced to purchase a product online.  The data were analyzed using the SEM-PLS approach. This study revealed that brand image and social media had positive and significant direct effect on purchase intention, and indirect effect on purchase intention mediated by EWOM. This study approved that brand image, social media and EWOM are key factors to increase product purchase intention during the covid-19 Pandemic.